Development of canned achara - Pe Benito Sharon Briones; Francisco, Ma. Leonora dL. (1999.)
The study was undertaken to develop canned achara. Sensory evaluation on three recipes was conducted to determine the most acceptable formulation for processing. Achara recipe from de Leon (1996) was chosen based on the highest mean score for general acceptability. The product was found to be moderately liked by the panelists. Thermal processing was conducted on the canned achara. The study adapted the UP Pilot Food Plant process as the preliminary processing, which included the hot-filling of the pickling solution. However, a revised processing, which combined the hot-filling and the exhausting methods, was devised since preliminary tests resulted to spoilage. The study found that hot-filling of the pickling solution at 212F and exhausting at 203F for 2 minutes made the product commercially sterile and organoleptically acceptable. Cut-out tests, microbiological examination and sensory evaluation were conducted to verify the processed product. Results of the cut-out tests showed no signs of spoilage. Microbiological results were within the acceptable range and were considered safe. Sensory evaluation showed that the product had favorable sensory characteristics.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Vegetables -- Preservation; Pickled foods, Canned